Italian Russian Studies and Russian Teaching at University: Analytical Review of Ten Years (2013–2023) of Research - Linda Torresin (Studi Slavistici, 2024)
This paper adopts a historical-critical approach to highlight the main trends and lines of development in Russian studies in Italy dedicated to the teaching of Russian as a foreign language (RFL) at universities. The research’s strengths, gaps, and challenges are emphasized to reveal new perspectives on language education. Specifically, we focus on the last decade (2013–2023) and the following areas: teaching of grammar and vocabulary and didactics of literature and culture. The examination of RFL research devoted to the Italian university context uncovered some specific insights. If we count the numerous studies dedicated to the teaching of grammar and vocabulary versus the didactics of literature and culture, the latter area has seen less success among Italian Russianists. Overall, the transversal and interdisciplinary character of many works and the variety of theoretical-methodological approaches employed can be considered the greatest strengths of the studies reviewed. However, more critical and non-essentialist positions should be explored in future research. Additionally, the field needs to pay greater attention to concrete teaching practices.